"Lightbulb Moments": The (Re)Conceptualization of Coach Development in Aotearoa, New Zealand - Fyall, G.; Cowan, J.; Bennett, B.; Hapeta, J.; Walters, S. (International Sport Coaching Journal, 2024)
Systems thinking is used extensively in organizational research as a framework to understand individual and organizational learning, adaptation, and change. However, systems thinking has had limited application in sport coaching research. In this study, we draw on a systems thinking framework to investigate Sport New Zealand`s recently conceptualized and implemented coach development program known as Coach Developer Aotearoa. To do so, we employ an interpretive phenomenological analysis to analyze the semistructured interview data gathered from the original six-member, Coach Developer Aotearoa design team. Our initial deductive analysis revealed that the participants acquired a more sophisticated understanding of coach development as they interrogated their own personal, collective, and societal assumptions. Specifically, concepts of learner-centeredness, active learning, and reflection, and a greater emphasis on cultural sensitivities replaced traditional behaviorist perspectives of coaching development. In our discussion, informed by our further abductive analysis, we describe the challenges faced by Sport New Zealand when looking to promote their new vision across the New Zealand sport landscape. In doing so, we offer emergent understanding and raise awareness about the possibilities that an alternative definition of critical reflection could offer when seeking systemic change on such a large scale.